One-year clinical outcome of biodegradable polymer sirolimus-eluting stent in all-comers population. Insight from the ULISSE registry (ULtimaster Italian multicenter all comerS Stent rEgistry). (1st June 2018) - Godino, Cosmo; Beneduce, Alessandro; Ferrante, Giuseppe; Ielasi, Alfonso; Pivato, Andrea Carlo; Chiarito, Mauro; Cappelletti, Alberto; Perfetti, Giulia; Magni, Valeria; Prati, Eugenio; Falcone, Stefania; Pierri, Adele; et al.
Abstract: Background: This study was designed to confirm in a large population of unselected patients the promising results of Ultimaster® biodegradable polymer sirolimus-eluting stent (BP-SES) already shown in previous trial. Methods: ULISSE is an observational, multicenter, national registry evaluating all patients undergoing PCI with the Ultimaster® BP-SES. Incidence of 1-year TLF (cardiac death or target vessel MI or clinically indicated TLR) was the primary endpoint. Pre-specified subgroup analysis was performed for diabetic patients and for those with lesion longer than 25 mm, bifurcation and CTO lesions. Results: 1660 patients were enrolled in 9 Italian cardiology centers, 82% were males, mean age of 68 ± 10 years, and 29% were diabetics. Overall 2422 lesions were treated, 65% type B2/C lesions, 7% CTOs, 17% bifurcations and 38% long lesions. The incidence of 1-year TLF was 5%, with 3.2% of clinically indicated TLR. TLF occurred in 8% of the patients with diabetes mellitus, and 7% in bifurcation, 6.7% in CTO and 6.2% in long lesions. Definite overall ST was 0.9%, and 1.2% in patients treated for type B2/C lesions. Multivariate logistic regression analysis identified stenting on unprotected LMT (OR = 4.80), stenting on ISR lesion (OR = 3.19) and need for rotational atherectomy (OR = 6.24) as the strongest independent predictors of TLF. Conclusions: The results of this national all-comers registry show that the Ultimaster® BP-SES real-world performance was comparable with that observed in the clinical trial, with low rate of primary endpoint and TLR. Long term follow-up will be necessary to prove the theoretical advantage of the BP-SES over time. Highlights: The ULISSE registry represents the first observational, multicenter registry evaluating clinical outcome of PCI with Ultimaster® BP-SES in an all-comers population; Ultimaster® BP-SES was mainly used in complex lesions (65%) and in patients with high-risk clinical profile; The incidence of primary endpoint (TLF) confirmed the observations of the CENTURY II trial; In the subgroup analysis, the Ultimaster® BP-SES had encouraging results also in DM patients, bifurcations, CTOs and long lesions; 1-year overall definite ST was rare (0.9%) and was slightly higher, although not significantly, in patients treated for type B2/C lesions.